Fast two-flip move evaluations for binary unconstrained quadratic optimisation problems. (20th July 2010) - Glover, Fred; Hao, Jin-Kao
We provide a method for efficiently evaluating two-flip moves that simultaneously change the values of two 0-1 variables in search methods for binary unconstrained quadratic optimisation problems (UQP). We extend a framework recently proposed by the authors for creating efficient evaluations of one-flip moves to yield a method requiring significantly less computation time than a direct sequential application of one-flips. A tabu search algorithm that combines one-flip and two-flip moves, in a study currently in process, has made use of this extension to produce very competitive results on some UQP benchmark instances.